Aplikasi Peringatan Dini Kebocoran Gas LPG untuk Rumah Tangga dengan Modul NodeMCU ESP32 - Tanumihardja, Wilbert Josef; Dasawati, Elis Sondang (Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
The development of technology is very rapid, starting from computers that can only perform mathematical calculations, to various smart devices that have become an integral part of everyday life. This development has brought many good benefits to human life. One example is the existence of early warning technology for disasters. Early warning is a very important element in risk management efforts.